Managing Assurance Information: A Solution Based on Issue Tracking Systems - Almendra, Camilo; Silva, Carla (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2020: Anais do XXXIV Simpósio Brasileiro de Engenharia de Software, 2020)
Context. Development of safety assurance cases (SACs) is a trending need for certification of safety-critical systems in regulated domains. Their development encompasses collecting, linking, and structuring diverse project information, such as requirements, hazards, and components. A key building block of SACs is the explanation behind requirements and design decisions, the so-called assurance rationale, which provides compelling argumentation on the system suitability for use. Late development of SACs leads to late discovery of hazards, risks, requirement and design issues that affect the system safety. Question/ problem. Current practice is to manage the assurance rationale in the SAC tools or artefacts, even though it is closely related to project and traceability information. This separation inhibits the shared understanding between safety and software professionals and may cause loss of rationale that results in a poor quality of certification documentation. It also hinders the automated SAC construction and assessment directly from project management tools. Principal ideas/results. This paper presents an approach to support the management of assurance rationale integrated with project information. Our approach defines an assurance rationale model that binds requirements, safety analysis information and assurance case elements. We show the use of the model applied to an issue tracking system. Contribution. We propose a new perspective on assurance cases management by bringing their building blocks into project management tools. Such integration could help bridge Safety and Software Engineering activities and avoid loss of rationale through the system life cycle. Also, it fosters the development of new approaches for SAC generation and assessment.